Születő város: Káposztásmegyer - Rigóczky, Csaba (Tér és Társadalom, 1996)
Nowadays Káposztásmegyer is a part of the Hungarian capital, struggling with a lot of problems, but achieving some advantages, too. It’s position is positive looking at the people, the local society (e.g. age-structure), or it’s achitectural profile, but negative if we see the infrastructural level, the isolation from the inner part of the capital. The improvemens in the near future may result a sudden development, some other people wait stagnation, the third opinion says that great mass of environmental pollution will come. The truth is: Káposztásmegyer is the city of the fututre, if we see the things on an optimistic way, or the pessimistic.